STUDI PROSEDUR PENILAIAN DOMAIN AFEKTIF OLEH GURU PAI DI SMP NEGERI 2 BANDUNG DAN SMP SALMAN AL-FARISI BANDUNG - Pajrin, Nur Anis Saila; Asyafah, Abas; Anwar, Saepul (TARBAWY : Indonesian Journal of Islamic Education, 2019)
Abstract. This article examines the procedure for evaluating the process and learning outcomes of Islamic Religious Education (IRE/PAI) in the affective aspect. In IRE/PAI, the assessment of affective aspect is still a problem. In fact, there are many obstacles in its application. This research uses a qualitative approach with descriptive methods. Data collection uses observation, interview, documentation, and triangulation techniques. Analysis of research data is carried out in the form of data reduction, data display, and verification. Based on the results of the study, it was found that the stage of the preparation of attitude assessment instruments in schools was in accordance with the established guidelines, but related to the design of the grid and analyzing the quality of the instrument was not optimally implemented. Then the implementation stage of the attitude assessment was generally applied according to the guidelines, although there were still obstacles that were not in accordance with the plan. Finally, the results stage of the attitude assessment process has been carried out according to the guidelines, but in terms of time control and objective assessment decisions need to be optimized.Â Abstrak. Artikel ini mengkaji prosedur penilaian proses dan hasil belajar Pendidikan Agama Islam (PAI) dalam aspek afektif. Dalam PAI, penilaian aspek afektif masih menjadi permasalahan. Pada kenyataannya, terdapat banyak kendala dalam penerapannya. Penelitian ini menggunakan pendekatan kualitatif dengan metode deskriptif. Pengumpulan data menggunakan teknik-teknik observasi, wawancara, dokumentasi dan triangulasi. Analisis data penelitian dilakukan dalam bentuk reduksi data, display data, dan verifikasi. Berdasarkan hasil penelitian, ditemukan bahwa tahap penyusunan instrumen penilaian sikap di sekolah sudah sesuai dengan pedoman yang ditetapkan, namun terkait perancangan kisi-kisi dan penganalisaan kualitas instrumen belum optimal terlaksanakan. Kemudian tahap pelaksanaan penilaian sikap, secara umum teraplikasikan sudah sesuai panduan, meskipun masih terdapat kendala yang tidak sesuai dengan rencana. Terakhir, tahap hasil dari proses penilaian sikap, sudah terlaksana sesuai pedoman, namun dalam hal pengendalian waktu dan keputusan penilaian yang objektif perlu dioptimalkan lagi.